The gospel according to Moses : theological and ethical reflections on the book of Deuteronomy - Block, Daniel Isaac, 1943- (Eugene, OR : Cascade Books, 2012)
These essays are concerned with broad hermeneutical and theological issues raised by the book of Deuteronomy.
Deuteronomy: a theological introduction -- Recovering the voice of Moses: the genesis of Deuteronomy -- Excursus A: The voices of Deuteronomy -- Excursus B: Evidence for writing in the book of Deuteronomy -- Will the real Moses please rise?: an exploration into the role and ministry of Moses in the book of Deuteronomy -- Preaching Old Testament law to New Testament Christians -- "You shall not covet your neighbor's wife": a study in Deuteronomic domestic ideology -- Excursus C: How shall we number the Ten commands? -- All creatures great and small: recovering a Deuteronomic theology of animals -- Other religions in Old Testament theology -- No other gods: bearing the name of YHWH in a polytheistic world -- "In spirit and in truth": the Mosaic vision of worship.
Companion volume: How I love your Torah, O Lord! : studies in the book of Deuteronomy.
Includes bibliographical references (p. 299-328) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Theology